The CENAME (Menstrual Panties) - Frida Yuliana; Happy Dwi Aprilina (Proceedings Series on Health & Medical Sciences, 2021)
Indonesia is the first country in its highest cases of cervical cancer in the world, and 62% of them was due to the use of a poor-quality sanitary napkins. There are 400 additional cervical cancer patients annually. Menstrual problems are also triggered by a poor quality sanitary napkins while menstruating and wearing regular sanitary napkins that have been mixed with chemicals and mixed with non-sterile materials from common sanitary napkins. Aim this research is to create a good quality of menstrual panties (named as CENAME). This research applied a research and development (R&D) method. A questionnaire trial on the panties to fertile women who were at menstruation period; they were 18 to 45 years old. The location was in Toyareka Village, Kemangkon District, Purbalingga. This research was carried out in December 2020. Most respondents were 18-20 and 21-30 years old (each with 2 persons), most of them had a high level of education (3 people). The product has passed a product testing of the health experts. The testing was to determine three aspects of comfort, capacity and hygiene. Its comfort level had an average score of 33.8, meaning very comfortable/excellent category. The producst has passed the testing of health experts. It has been proved to overcome an irritation which was usually caused by a regular disposable sanitary napkin and it surely minimizes the waste. The selection of the materials must be highly-considered.